Islamic banks’ fee income, characteristics and risk: Panel data analysis evidence from Indonesia / Siti Sarah Mat Isa, Masturah Ma’in and Azlina Hanif. - Mat Isa, Siti Sarah; Ma’in, Masturah; Hanif, Azlina (Universit Teknologi MARA Cawangan Selangor, 2018)
One of the non-operating income in Islamic banking operation, which is fee income has become progressively vital in expanding their income to counter decreasing net earnings due to rivalry from other financial competitors. However, it is important for Islamic banks to find out any potential risk that will distress their performance due to this activity. This is because, mixed results on this issue derived from the previous studies especially in the Western context such as in the US, Germany and other European countries. Using Indonesian Islamic bank’s quarter data between 2009 and 2013, this study adopts the panel data regression analysis to examine the relationship between Indonesian Islamic banks fee income and risk. The empirical results signified that fee income activities able to reduce Indonesian Islamic bank’s risk.